RELEVANSI TEORI FREE TRADE DALAM PERSPEKTIF ISLAM - Ajeng Puspa Marlinda (Jisiera: The Journal of Islamic Studies and International Relations, 2017)
This study focuses on the relevance of free trade in an Islamic perspective. However, in the first explanation of free trade will be examined from the point of view of several theories of international relations such as realism, liberalism, socialism, and marxism. After that explanation, then free trade will be presented in general according to Islamic perspective. Whether good or bad, and what may or may not be in the free trade itself according to Islamic views. In this paper, the discussion will try to analyze free trade in Islamic perspective in terms of ontology that is the reason of what or what is free trade according to Islam, then epistemology which talk about the forms of free trade allowed Islam, and last from the axiological aspect that is About what the benefits of free trade are viewed from an Islamic perspective.